2-[3-(2-chloroethyl)-3-nitrosoureido]-1,3-propanediol (chlonisol): blood content in rats after intravenous administration and chemical resistance - V. A. Alexandrov; G. V. Tochilnikov; S. V. Shatik; A. N. Stukov; O. A. Beljaeva; E. V. Bashkatova; V. G. Dranishnikov; T. Yu. Semiglazova (Фармакокинетика и Фармакодинамика)
Background. The domestic antitumor compound 2-[3-(2-chloroethyl)-3-nitrosoureido]-1,3-propanediol (chlonisol) has high antitumor activity on a wide range of experimental tumors.Goal. To study the content of chlonisol in the blood of rats at different times after intravenous administration and its chemical stability in 0.9 % sodium chloride solution, urine and blood serum.Methods. The concentration of chlonisol in various media was determined by HPLC. In vivo studies on 10 male rats with a body weight of 180–200 g. the concentration of chlonisol in the blood of rats was determined 2, 30, 60, 90 and 120 minutes after its intravenous administration at a dose of 40 mg/kg. In in vitro experiments, a 0.1 % solution of chlonisol was incubated at 37 °C in three media: 0.9 % sodium chloride solution, blood serum and urine. Aliquots were selected at different intervals and analyzed for the content of chlonisol. The stability of chlonisol was evaluated in relation to its concentration before and after incubation, expressed as a percentage.Results. When chlonisol was administered intravenously at a dose of 40 mg/kg to rats, its complete disappearance from the blood was observed within 2 hours. The half-life was 27 minutes. Of the three media studied in vitro experiments, chlonisol was the most stable in 0.9 % sodium chloride solution(89 % of the initial level after 10 hours of incubation at 37 °C). Less stable, but for a long time – in urine (60 % of the initial after 1 hour of incubation and 37 % after 2 hours). The lowest resistance of chlonisol was in the blood serum (a decrease in concentration to 11 % after 1 hour and to 0 after 2 hours of incubation).Conclusion. The results obtained allow us to make assumptions about possible ways of using chlonisol: The high stability of chlonisol in 0.9 % sodium chloride solution will allow its long-term drip intravenous infusions, as well as perfusion intraarterial chemotherapy. Maintaining the concentration of chlonisol in urine at 60 % of the initial level for 1 hour will allow the use of intravesical instillations of chlonisol in superficial bladder cancer.